Occurrence, Virulence and Drug Resistance Characterization of Non-typhoidal Salmonella in Poultry and Environmental Samples of Rewa City, India - Sharma, S.; Dixit, B.; Rawool, D.; Singh, R. V.; Shrivastav, N.; Mishra, A. K.; Kaushik, A.; Dixit, M. (International Journal of Bio-resource and Stress Management, 2024)
The Experiment was conducted during June–December, 2022 at Department of Veterinary Public Health & Epidemiolgy, College of Veterinary Science & Animal Husbandry, Rewa, NDVSU, Jabalpur, M.P. India. to attribute the possible risk of poultry and its product as an increasing cause for food borne Salmonellosis, a cross sectional study was carried out in poultry samples from Rewa city of Madhya Pradesh. A total of 300 sample (Poultry and environment) were collected and processed for isolation and identification of Salmonellae by culture, biochemical methods and molecular methods. Only poultry samples were found positive while all the environmental sample were negative. A total of 5.5% occurrence of Salmonella was found in poultry samples with 5% positivity in meat sample and 6% in the caecum. Two serotype Salmonella Typhimurium (4%) and Salmonella. Infantis (1.5%) were detected. Drug resistance pattern of isolated Salmonella indicated a very high resistance towards many of antibiotics which are critical for clinical use for animal, birds and humans as well. All the isolates were positive for Virulence marker invA, spiA, and drug resistance gene, blaTEM, while ampC and tetA were detected only in S. Typhimurium with 23 and 50% positivity and spvR and spvC virulence genes were not detected in any isolated salmonella. As Non typhoidal Salmonella are of zoonotic importance, their presence in poultry meat and fecal samples, indicating the need to implement effective prevention and control measures throughout food chain that is from farm to fork level.